Utilizing Data and Data Science to Optimize Tune In - Salon, Data; Salon, Data (Data Science Salon, 2019)
Presented by Diane Leung, Principal, Analytics Innovation at Altman Vilandrie & Company Measuring and optimizing tune-in is critically important for the media and entertainment industries. This discussion focuses on best practices for utilizing data and machine learning to optimize tune-in on national linear inventory. In order to do this properly, advertisers need to unify their marketing ecosystem, design a holistic measurement approach, and break down barriers for closed-loop, incremental measurement. In this session you will learn how to: 1) Create a framework for utilizing data and machine learning to maximize tune-in and 2) Overcome analytical obstacles created from fragmented and incomplete data.